2009
DOI: 10.1016/j.bmcl.2009.05.107
|View full text |Cite
|
Sign up to set email alerts
|

First experimental identification of Ras-inhibitor binding interface using a water-soluble Ras ligand

Abstract: By combining in the same molecule Ras-interacting aromatic moieties and a sugar, we prepared a water-soluble Ras ligand that binds Ras and inhibits guanine nucleotide exchange. With this compound it was possible to determine experimentally by a (15)N-edited HSQC NMR experiment the ligand-Ras binding interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Although several previous studies have reported potential small-molecule association with Ras, none have characterized the binding site by a high-resolution structure analysis and none reported a defined binding pocket (3)(4)(5)(6)(7). The best-characterized Ras-binding compounds reported so far are SCH54292 (16) and its more water-soluble derivative (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several previous studies have reported potential small-molecule association with Ras, none have characterized the binding site by a high-resolution structure analysis and none reported a defined binding pocket (3)(4)(5)(6)(7). The best-characterized Ras-binding compounds reported so far are SCH54292 (16) and its more water-soluble derivative (7).…”
Section: Discussionmentioning
confidence: 99%
“…The best-characterized Ras-binding compounds reported so far are SCH54292 (16) and its more water-soluble derivative (7). In silico calculation based on NMR mapping suggests that these compounds bind to a region between switch II and helix 4 of Ras GDP , although other binding areas cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Judged from our HADDOCK docking models and the available co-crystal structures, it seems highly likely, that these different ligands, including Bisphenol A, bind to GDP-Ras and interfere with SOS complex formation due to steric reasons. Interestingly, the observed affinity of Bisphenol A is in the same micromolar range as the affinity between Ras-GDP and the SOS molecule itself (Palmioli et al, 2009). …”
Section: Low Molecular Weight Compounds As Functional Modulators Of Smentioning
confidence: 99%
“…Moreover, on the basis of these measurements only, the Ras protein was believed to be undruggable, since it lacks hydrophobic cavities on its molecular surface (Cox et al, 2014). Nevertheless, during the past years several small molecules and zinc-chelating compounds have been identified and characterised as Sos antagonists of K-Ras (Palmioli et al, 2009;Rosnizeck et al, 2012). In 2012, co-crystal structures of several ligands bound to the fulllength and truncated Ras were published (Maurer et al, 2012;Sun et al, 2012).…”
Section: Low Molecular Weight Compounds As Functional Modulators Of Smentioning
confidence: 99%
“…Some small-molecule inhibitors of KRAS have been identified [53], including development of potential irreversible inhibitors of KRAS G12C mutant protein [54,55]. Although these new drugs seem to be effective in vitro, there is a need for further clinical studies and new drugs with increased affinity [56].…”
Section: Inhibition Of Ras Functionmentioning
confidence: 99%